Current changes in work environment and individual well-being: how to thrive in times of uncertainty? - Maslić Seršić, Darja (Array, 2012)
What is the psychological meaning of job insecurity, job loss and unemployment? Specifically, this talk will explore the subjective, perceived meanings of these phenomena. The impact of job insecurity, job loss and unemployment on individual well-being and work behavior will be described. Finally, more and less successful coping strategies will be explained, as well as the factors that moderate them.